The role of ICT in scaling social enterprises in India - PALIWAL, MS. SURABHI; NIYOGI, SHYAMALENDU (The journal of contemporary issues in business and government, 2021)
With growing interest of analysts and researchers in social entrepreneurship, the hope for its rapid development is also increasing. Various research studies have discussed in detail how there exists a dire need for social enterprises to fill in the gap that traditional political and commercial solutions fail to do sufficiently. Thus the developing ecosystem of social enterprise is an answer to the grave problems of poverty, sanitation, education, health, unemployment etc. The approach of social enterprises where commercial strategies are applied to achieve social objectives, has gained so much attention its not something very new, but definitely effective in bringing change ( Rymsza, 2005; Thompson et al., 2000). Social enterprises have the potential to provide unique, frugal and low cost potential solutions to various social problems through a pragmatic market approach. Their way of working targets two concerns: birth of simpler and practical solutions to a severe problem such as invention of low cost incubators to be used in rural areas and financial sustainability of social enterprises ensuring their presence in the market. It will be fair to say that in the recent years of development, the field of social development has used ICTs (Information and Communication Technologies (ICTs) vary aptly from radios to mobile phones- to smart phone to create impact in the lives of human beings. ICT based devices and their application enable us to find novel commercial ideas, sustainable business models, and low cost strategies of scaling up. The flexibility and innovativeness of ICT make it a strong tool for social enterprises to experiment with and hence this powerful integration has resulted in some spectacular organisations providing solutions to some of the most critical issues such as poverty and education. The objective of this research paper is to analyse how the ICTs can support social enterprises to improve their performance, the impact creation and scaling of social enterprises through: • Analysis of different social enterprises with business models based on ICT have affected the performance and impact of the organisation • Analysis of efficient ICT tools that provide the boost in the design, management and performance of social enterprises